The Influence of Education and Career Development on Personnel Performance in The Special Detacion 88 Anti-Terror of The Republic of Indonesia Police - Yanto Hermawan; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
The objectives of this study are: To determine and analyze the influence of education on personnel performance, to determine and analyze the influence of career development on personnel performance, and to determine and analyze the simultaneous influence of education and career development on personnel performance. The test statistics used were as follows: There is an influence of training on work behavior, this can be seen from the t count value for Education (X1) of 4.858 while the t table value for n = 71 is 1.950. So 4.858> 1.950, then H0 is rejected and Ha is accepted, it can be stated that Education (X1) has a significant effect on personnel performance (Y), the t count value for Career Development (X2) is 9.758 while the t table value for n = 71 is 1.950. So 9,758> 1,950, then H0 is rejected and Ha is accepted, It can be stated that Career Development (X2) has a significant effect on Personnel Performance (Y). The R-square (R2) value is 0.742. This indicates that 74.2% of Education (X1) and Career Development simultaneously influence Personnel Performance (Y), while the remaining 25.8% is influenced by other factors not examined in this study.